Family and their roles in the nursing care for children living with chronic diseases - Dr. Ilya Krisnana (Universitas Airlangga, 2026)
The burden that children with chronic illness face is not limited to the effectiveness of pharmacological interventions. The burden that families and healthcare providers face is further compounded by fears and apprehensions that are not necessarily made manifest through speech. In this editorial, we shall seek to explore the implications that high-quality nursing care have for children patients with chronic illness. The discussion shall not be limited to the care and management of the illness itself but shall seek to explore the holistic nature of living with a chronic illness. There are several issues that need to be highlighted with greater intensity. These issues include: the integration of the family as a genuine partner in care, the intentional use of technology as a means of engaging families within their natural environment, and the psychological burden that paediatric chronic illness has on children as well as families. The nursing profession has tremendous potential that can be made in this area, as long as it is done so appropriately. Keywords: chronic disease; child; family-centered care; paediatric nursing